Pidgin Language and the Phenomena of Pidginization in the Second Language Acquisition Process - Mayang Pipit (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2024)
Pidgin is a language which has no native speakers. The structure of the language, in the level of phonology, morphology, syntax and semantics, is as simple as its function as a tool of conveying referential and denotative meaning only. In this research, pidgin was discussed on the perspective of second language acquisition through two related theories; Acculturation Model and Nativization Model. This research used a qualitative approach with descriptive and literature review method. Through this research it was found that Pidgin, with its simple structure, primarily served as a utilitarian tool for trade transactions, conveying referential meanings rather than social distinctions or politeness. In second language acquisition, Pidginization emerged early in the learning process, supported by two theories: the Acculturation Model focusing on language input and social factors, and the Nativization Model considering cognitive dimensions in the learner's language processing.